(untitled) (International Journal of Innovative Technologies in Economy, 2024)
Anthropogenic impact did not go beyond water resources therefore, the study of water resources and its rational use is of great importance for the development of the country. Ajara is one of the most beautiful and strategically important regions of Georgia due to its location, wealth of flora and fauna, tourism and recreation. In this region we find a hydrological network of medium length and small rivers. As a result of anthropogenic influence, the river water is polluted both chemically and biologically. The practical significance of this research is as follows: determination of the level of biological pollution for monitoring the quality of surface water in the Ajara region, laboratory analyzes and inspection of river basins, after which a plan and cost estimate will be developed, what financial resources will be needed for laboratory studies of existing pollution. As a result of the mentioned studies, the foundation will be laid for the creation of databases on the state of rivers in the Ajara region, based on which it will be possible to plan and carry out future works, which in turn will definitely have a positive impact on the local population and the interests of the country. The Autonomous Republic of Ajara was selected for the study, where for the first time the main polluting circumstances and sources of a certain number of rivers are observed and the underlying causes determined. 10 independent catchment rivers were selected for pollution study using laboratory analysis. In each river, laboratory sampling points were selected and laboratory analyzes were carried out for pH, E. coli, nitrites, total coliform bacteria and streptococci parameters. The article presents the results of the research process and the cost per sampling location, totaling the cost for 10 rivers that will be needed to continue the mentioned studies in the future. The article is completed with the support of the Shota Rustaveli National Science Foundation of Georgia (SRNSFG). Project No. PHDF 22-2127.